Aided communication, mind understanding and co-construction of meaning. (17th November 2022) - Stadskleiv, Kristine; Batorowicz, Beata; Sandberg, Annika Dahlgren; Launonen, Kaisa; Murray, Janice; Neuvonen, Kirsi; Oxley, Judith; Renner, Gregor; Smith, Martine M.; Soto, Gloria; van Balkom, Hans; Walter, Catia; et al.
ABSTRACT: Mind understanding allows for the adaptation of expressive language to a listener and is a core element when communicating new information to a communication partner. There is limited knowledge about the relationship between aided language and mind understanding. This study investigates this relationship using a communication task. The participants were 71 aided communicators using graphic symbols or spelling for expression (38/33 girls/boys) and a reference group of 40 speaking children (21/19 girls/boys), aged 5;0–15;11 years. The task was to describe, but not name, drawings to a communication partner. The partner could not see the drawing and had to infer what was depicted from the child's explanation. Dyads with aided communicators solved fewer items than reference dyads (64% vs 93%). The aided spellers presented more precise details than the symbol users (46% vs 38%). In the aided group, number of correct items correlated with verbal comprehension and age.